Methodological considerations for the planning of metropolitan areas (2009)
The orientation and expansive form in which the land use is developed in metropolitan areas, in virtue of the increment in the settlers rate of growth, represents a challenge for the local and statal Latin Americans governments, mainly if it’s consider the flexibility of the existing planning controls; for these reason it is of fundamental importance to advance in the knowledge of methodological processes that help in the site planning.